2008
DOI: 10.1111/j.1745-7270.2008.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ornithine decarboxylase in breast cancer

Abstract: Role of ornithine decarboxylase in breast cancerActa Biochim Biophys Sin (2008): 235-243 |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 23 publications
(16 reference statements)
3
17
0
Order By: Relevance
“…We also confirm the results of previous studies on SSAT and ODC enzyme activities carried out in human BC tissues compared with nonmalignant control, indicating a high ODC and SSAT activities in BC samples [12,38,39]. Manni et al [38] reported that increased ODC activity is associated with an increased risk of both disease recurrence and death, while Deng et al [39] showed that the overexpression of ODC in BC tissues correlates with the TNM grading system. Wallace et al [12] reported that the decrease of APAO activity in BC tissues positively correlated with the aggressiveness of the tumor, while the increase of SSAT activity showed a tendency to be indicative of a poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…We also confirm the results of previous studies on SSAT and ODC enzyme activities carried out in human BC tissues compared with nonmalignant control, indicating a high ODC and SSAT activities in BC samples [12,38,39]. Manni et al [38] reported that increased ODC activity is associated with an increased risk of both disease recurrence and death, while Deng et al [39] showed that the overexpression of ODC in BC tissues correlates with the TNM grading system. Wallace et al [12] reported that the decrease of APAO activity in BC tissues positively correlated with the aggressiveness of the tumor, while the increase of SSAT activity showed a tendency to be indicative of a poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…These metabolites were also found to be significantly elevated in breast cancer tissue compared to normal tissue in a previous study that investigated a large cohort of breast cancer cases [8]. Via the action of ornithine decarboxylase (ODC), ornithine is the starting point for the synthesis of polyamines that are associated with tumor promotion and progression [18]. That study found that the level of ODC expression was highest in MDA-MB-231 cells, which implies that ornithine plays an important role in determining tumor growth and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…We found that NCAO had a highly potent antitumoral effect when tested in vitro against 13 tumor cell lines of diverse tissue origin (from humans and mice) and when tested in vivo in a mouse model using both solid and ascitic tumors. We selected cancer cell lines of various origins in which deregulation of cell proliferation was related to overexpression and high activity of ODC and that are representative of many cancers [10], such as MDA-MB-231 in breast cancer [22], HeLa in cervical cancer [23], and Raji in lymphoblastoma [24]. The NCAO exerted an in-vitro cytotoxic effect against cancer cell lines, irrespective of their origin, after 72 h of exposure.…”
Section: Discussionmentioning
confidence: 99%